Advanced Cell Therapies for Glioblastoma - Wang, Guangwen; Wang, Wenshi (Frontiers in Immunology, 2022)
The sheer ubiquity of Gioblastoma (GBM) cases would lead you to believe that there should have been many opportunities for the discovery of treatments to successfully render it into remission. Unfortunately, its persistent commonality is due in large part to the fact that it is the most treatment-resistant tumors in adults. That completely changes the treatment plan of attack. Long established and accepted treatment therapies such as surgical resection, radiation, and aggressive chemotherapy, (and any combination thereof) have only confirmed that the disease lives up to its treatment-resistant reputation. To add to the seemingly insurmountable task of finding a cure, GBM has also proven to be a very stubborn and formidable opponent to newer immunotherapies. Across the board, regardless of the therapy combination, the five-year survival rate of GBM patients is still very poor at a heartbreaking 5.6%. Obviously, the present situation cannot be tolerated or deemed acceptable. The grave situation calls for researchers to be more innovative and find more efficient strategies to discover new and successful strategies to treat GBM. Inspired by researchers worldwide attempting to control GBM, we provide in this review a comprehensive overview of the many diverse cell therapies currently being used to treat GBM. An overview of the treatments include: CAR T cells, CAR NK cells, gamma-delta T cells, NKT cells, dendritic cells, macrophages, as well stem cell-based strategies. To give you the complete picture, we will discuss the efficacy, safety, and developmental stages, the mechanisms of action and the challenges of each of these therapies and detail their potential to be the next-generation immunotherapeutic to eliminate this dreadful disease.